Gallbladder tuberculosis mimicking cholecystitis: A case report - Nur Prasetyo Nugroho; Tutik Kusmiati; Santoso Santoso (National Scientific Medical Center, 2021)
Abstract Tuberculosis can affect extrapulmonary organs. Gallbladder tuberculosis is one of the rare extrapulmonary tuberculosis. Fewer than 120 cases have published since reported in 1870. We reported a 55-year-old woman who came to the hospital with a chief complaint of right upper abdominal pain. The abdominal ultrasonography obtained gallstones. The patient was initially diagnosed with acute cholecystitis, and laparoscopic cholecystectomy was performed. The histopathologic examination of the gallbladder showed chronic cholecystitis inflammation cells, while the smear showed acid-fast bacilli. The primary diagnosis was gallbladder tuberculosis. Antituberculosis treatment was performed with good clinical outcome and radiological improvement.